Diastereoselective Johnson–Corey–Chaykovsky trifluoroethylidenation1. Issue 66 (25th August 2015) - Duan, Yaya; Zhou, Bin; Lin, Jin-Hong; Xiao, Ji-Chang
<x xml:space="preserve">Abstract</x> Johnson–Corey–Chaykovsky trifluoroethylidenation with (2, 2, 2-trifluoroethyl)diphenylsulfonium triflate proceeded smoothly to afford trifluoromethyl-epoxides, -cyclopropanes and -aziridines with excellent diastereoselectivity.